Development of a Low-Cost Stationary Laser Scanning System for Generation of Building Information Models - Syed Riaz un Nabi Jafri; Muhammad Owais Ali Siddiqui; Faraz Akbar; Abdul Basit; Sheraz Shamim; Saad Ahmed (Elektronika ir Elektrotechnika, 2022)
This paper presents a method for developing a 3D point cloud map of any indoor and outdoor vicinities using an indigenously developed stationary scanning system comprising of a single low cost 2D laser scanner. The data logging of scanner and required inertial measurement units (IMUs) has been carried out using a Robot Operating System (ROS). Multiple divergent environments have been scanned and 3D point clouds have been developed, which have been found accurate when compared to the ground truth. In addition, the Building Information Model (BIM) of the surveyed vicinities have been developed using generated point clouds. Compared to available surveying solutions present in the local market, the developed system has been found accurate, faster, economical, and user-friendly to generate structural results of the surveyed vicinities in detail.